Machine design design of machine elements - Jalaludeen, S. Md (Anuradha Publications, 2011)
In this book the design of common machine elements such as shafts, couplings, riveted and welded joints, pressure vessels, spring, crankshaft, flywheel, etc. have been discussed in detail in an exceptionally simple manner with the aid of fundamental theories, simple procedure and numerous problems relating to various feilds of engineering and science.